Weaving the literacy Web : Changes in reading from page to screen - Sutherland-Smith, Wendy (The Reading Teacher, 2002)
Teachers differ widely in their attitudes toward and abilîty to cope with technology. ln the case of Internet technology, changes have swept Ihrough Australian schools at an unprecedented pace. Inevitably, the roie of the classroom teacher is also affected, and indeed altered. Additionally, in Australian schools, there appears to have been a tangible shift from pen-and-paper writing to digital text production, which also relocates traditional teaching parameters. This shift in the mode of textuai production has prompted me, as a teacher, to consider whether my students use different strategies when reading print text than when reading digital text. Further, it raises the question about reading strategies: Should I teach different reading strategies in the computerbased classroom? If so, what different strategiesare required?
Keywords: écriture et lecture numériques; enseignement; lecture numérique; stratégie de lecture